THE DEVELOPMENT OF CLARIUM STAIN CELLS IN SALINE WATER (CLARIAS GARIEPINUS BURCHELL, 1822) - Faxriddin Mamadov; Xushnid Ayasov; G‘. Qultoyev; D. Mamanov; G‘. Yaxshibekov (Zeta Repository, 2023)
The article presents the results of experiments aimed at solving such problems as increasing fish productivity through the use of salt water in fisheries. Data on the level of survival of clarias catfish fry in waters with different salinity were analyzed, the results obtained can be used in practical work on fish farming in intensive aquaculture systems. Especially in salty water bodies, when growing commercial fish of clarias catfish, such a scientific result was obtained as the survival of fry resistant to salinity based on the stage of development, from their weight.